2020
DOI: 10.1177/0093854820903752
|View full text |Cite
|
Sign up to set email alerts
|

Youth Perceptions of Law Enforcement and Worry About Crime from 1976 to 2016

Abstract: Recent unjust interactions between law enforcement and youth of color may have provoked a “crisis” in American law enforcement. Utilizing Monitoring the Future’s data on distinct, cross-sectional cohorts of 12th graders from each year spanning 1976–2016, we examined whether youth perceptions of law enforcement have changed. We also traced youth worry about crime considering declining perceptions of law enforcement may correspond with increasing worry about crime. Across decades, White youth consistently percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 63 publications
(95 reference statements)
2
21
0
Order By: Relevance
“…Other studies show that young people have a negative bias toward authority figures (Fagan & Tyler, 2005;Fine et al, 2020). Dirikx et al (2012) suggest that negative attitudes toward the police may be normative or "part of the deal" among young people and authority figures, rather than definitive judgements of policing.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies show that young people have a negative bias toward authority figures (Fagan & Tyler, 2005;Fine et al, 2020). Dirikx et al (2012) suggest that negative attitudes toward the police may be normative or "part of the deal" among young people and authority figures, rather than definitive judgements of policing.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts could reduce the public’s perceptions of police bias. However, in an age where confrontations between police and young people are at the fore of the national conversation (Fine, Donley, Cavanagh, & Cauffman, 2020; Fine, Rowan, & Simmons, 2019; Friedman, 2017), police are encouraged to eliminate bias in their interactions with the community in the first place and to build relationships with youth in nonenforcement contexts (Fine, Padilla, & Tapp, 2019). These actions may reduce youths’ reliance on behavioral and attitudinal repertoires that promote violence as well as improve crime reporting (Kwak, Dierenfeldt, & McNeeley, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicated that individuals who identified as Black, non-White were more likely to hold negative perceptions and attitudes toward the police compared to Whites, regardless of the operationalization of the personal attitudes and dependent variables about the police, which included confidence, performance and experiences/encounters with law enforcement. Moreover, studies have found that Hispanics have more positive views of police than Blacks but still view the police less favorably than Whites (Rosenbaum et al, 2005;Fine et al, 2020). Research on perceptions of police among racial/ethnic groups other than Whites, Blacks and Hispanics has produced mixed results.…”
Section: Pijpsm 435mentioning
confidence: 99%